Determination of enantiomeric excess and diastereomeric excess via optical methods. Application to α-methyl-β-hydroxy-carboxylic acids. Issue 6 (25th January 2023) - Moor, Sarah R.; Howard, James R.; Herrera, Brenden T.; McVeigh, Matthew S.; Marini, Federico; Keatinge-Clay, Adrian T.; Anslyn, Eric V.
Abstract : Characterization of chiral molecules in solution is paramount for measuring reaction success. Abstract : Characterization of chiral molecules in solution is paramount for measuring reaction success. However, techniques to distinguish between chiral molecules containing more than one stereocenter through the use of optical techniques remains a challenge. Herein, we report a technique using a series of circular dichroism spectra to train multivariate regression models that are capable of predicting the complete speciation of 3-hydroxy-2-methylbutanoic acid stereoisomers. From this, it is possible to rapidly and accurately determine the enantiomeric excess and diastereomeric excess of the solution without the need for chiral chromatography.